Role of Electro-Diagnostic Tests In Early Detection of Diabetic Neuropathy - Ali, Zahed; Hakim, Maliha; Islam, Monirul; Bhowmik, Nirmalendu Bikash; Nahar, Shamsun; Ullah, AKM Anwar; Haque, Anisul (Bangladesh Journal of Neuroscience, 2009)
Since the peripheral nerve has the ability to regenerate, therapeutic intervention at earlier stages expected to have a better result in the treatment of diabetic neuropathy. So early detection of diabetic neuropathy is one of the major goals in its management. Purpose: The purpose of present study is to evaluate the efficacy of the electrodiagnostic tests to detect diabetic neuropathy at an early stage (before development of the signs of neuropathy). Method: 30 diabetic patients with or without symptoms of diabetic neuropathy were included in the test group. Diabetic patients with signs of neuropathy and with other complications, like stroke, peripheral vascular diseases were excluded. Twenty six control subjects (non-diabetic with no family history of diabetes) were included. Both the groups were matched for age. To see the functional status of peripheral nerves motor nerve conduction velocity (NCV), compound muscle action potentials (CAMP) of median nerve were studied. Sensory nerve conduction velocities (NCV), and sensory nerve action potential (SNAP) of median and sural nerves were also measured. Results: Sensory nerve conduction velocity of sural nerve was significantly slowed (43.84±8.23 vs 48.23±5.03 m/sec, p < .05) in diabetic patients. Sural sensory nerve action potential has lower in amplitude (13.31±7.03 vs 14.24±4.714 mv, p<.3) in diabetic patients. Median sensory nerve conduction velocity did show difference (50.89+8.23 vs 57.17±6.67 m/s, p < .01) and median sensory nerve action potential has significantly lower in amplitude (3.86±1.016 vs 7.39±4.79, p < .001) in diabetic patients. No significant difference was found in median nerve motor conduction velocity between the two groups of subjects. Amplitude of compound muscle action potential of median nerve also shows no significant variations.Considering mean±SD value of conduction parameter as the cut off value, sural nerve sensory conduction velocity was found slowed in 8 diabetic subjects (26%). Sural nerve sensory action potential was of lower amplitude in 12 diabetic subjects (40%). Eleven diabetic subjects (36%) had lower amplitude for median sensory nerve action potential (SNAP). For compound muscle action potential (CAMP) and sensory nerve action potential (SNAP) half the mean value of control was the cut off point. Conclusion: The result suggests that in diabetic patients of Bangladesh with or without symptoms of neuropathy, abnormalities of nerve conduction parameters can be detected early by routine electrodiagnostic monitoring. Sensory nerve conduction parameters are affected more than motor ones. Amplitude abnormalities are slightly more common than conduction velocity or latency abnormalities for sensory studies. Lower extremity nerves were affected more. Sural median nerve has the highest abnormalities in diabetic patients with early neuropathy. DOI: http://dx.doi.org/10.3329/bjn.v24i1.3038 Bangladesh Journal of Neuroscience 2008; Vol. 24 (1) :34-44